2022
DOI: 10.1016/j.respol.2021.104373
|View full text |Cite
|
Sign up to set email alerts
|

Innovative events: product launches, innovation and firm performance

Abstract: In this paper, we shed new light on the links between firm-level innovation and growth. We introduce data that capture a difficult-to-observe aspect of firms' innovative activity -new product/service launches -at scale. We show that our novel measures complement existing innovation metrics. We build a simple framework covering firm-level innovation, launches and revenue productivity. Then, we show positive linkages between past patenting and launches and between launches and performance for a large panel of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 95 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…Second, the process of how the information from each data source is linked to characterise those actors is explained. This work builds upon and extends the work by Dernis et al (2021[18]), Samek et al (2021[25]), Squicciarini and Nachtigall (2021 [24]), Nakazato and Squicciarini (2021 [17]) and Dernis et al…”
Section: Existing Evidence On Ai Adoption By Firmssupporting
confidence: 71%
See 1 more Smart Citation
“…Second, the process of how the information from each data source is linked to characterise those actors is explained. This work builds upon and extends the work by Dernis et al (2021[18]), Samek et al (2021[25]), Squicciarini and Nachtigall (2021 [24]), Nakazato and Squicciarini (2021 [17]) and Dernis et al…”
Section: Existing Evidence On Ai Adoption By Firmssupporting
confidence: 71%
“…In particular, trademarks can shed light on the extent to which (new) companies and products appearing on the market rely on, exploit or propose AI-related goods and services. In this context, Nakazato and Squicciarini (2021 [17]) exploit trademark applications filed at the European Union Intellectual Property Office (EUIPO), the Japan Patent Office (JPO) and the USPTO over the period 2009-18 and show that AI-related goods and services have expanded in consumer markets in recent years, especially protecting computer-related products or services, such as software or audiovisual devices. Combining AI-related patents and trademarks, Dernis et al (2021[18]) highlight that developments of AI technologies, goods and services is mainly due to start-ups or large incumbents, located in selected countries, with a majority of actors operating in ICT-related sectors.…”
Section: Existing Evidence On Ai Adoption By Firmsmentioning
confidence: 99%
“…Theoretically, this research contributes to the scholarly discourse regarding innovation and performance of Chinese enterprises operating in China ( Cai et al, 2019 ; Nathan and Rosso, 2022 ; Shuiliu et al, 2022 ) by providing evidence on the relationship that exists between innovation and the performance of Chinese enterprises. Previous studies have not fully paid attention to how the innovative effort of firms in China influences their production capabilities.…”
Section: Conclusion and Discussionmentioning
confidence: 79%
“…Notwithstanding the position of extant knowledge on the role of innovation in the performance of firms ( Grigorios et al, 2019 ; Nathan and Rosso, 2022 ), findings regarding the relationship between innovation and output of Chinese enterprises are still inconclusive ( Chiva et al, 2014 ; Piening and Salge, 2015 ; Yuefang et al, 2020 ; Chao et al, 2022 ; Shuiliu et al, 2022 ) and more remain to be understood about what triggers firms’ decision to be innovative. What has not been established clearly in literature is the impact of the innovative efforts of Chinese enterprises on their outputs.…”
Section: Introductionmentioning
confidence: 99%
“…A different thing is found in the research of Setiawan & Hartanto (2020) and Christian & Justinius (2021), the results of the study state that innovation does not affect competitive advantage. Research on the relationship between innovation and the performance of a company, especially MSMEs, is carried out by Zainurossalamia et al (2016); Chen et al (2018); Rofiaty (2019); Sumarni et al (2020); Nathan & Rosso (2022) state that innovations produced by a company or organization will have a positive and significant impact on the performance of the company or organization. However, there are inconsistencies in the results of research on innovation and company performance, this is found in research by Ali et al (2016) andPrima Lita et al (2020) that state that innovations in a company do not have a significant effect on company performance.…”
Section: Introductionmentioning
confidence: 99%